A cyclic di-GMP-binding adaptor protein interacts with a N5-glutamine methyltransferase to regulate the pathogenesis in Xanthomonas citri subsp. citri - Shi, Yu (2024)
The second messenger cyclic diguanylate monophosphate (c-di-GMP) regulates a wide range of bacterial behaviours through diverse mechanisms and binding receptors. Single-domain PilZ proteins, the most widespread and abundant known c-di-GMP receptors in bacteria, act as trans-acting adaptor proteins that enable c-di-GMP to control signalling pathways with high specificity. This study identifies a single-domain PilZ protein, XAC3402 (renamed N5MapZ), from the phytopathogen Xanthomonas citri subsp. citri (Xcc), which modulates Xcc virulence by directly interacting with the methyltransferase HemK. Through yeast two-hybrid, co-immunoprecipitation and immunofluorescent staining, we demonstrated that N5MapZ and HemK interact directly under both in vitro and in vivo conditions, with the strength of the protein-protein interaction decreasing at high c-di-GMP concentrations. This finding distinguishes N5MapZ from other characterized single-domain PilZ proteins, as it was previously known that c-di-GMP enhances the interaction between those single-domain PilZs and their protein partners. This observation is further supported by the fact that the c-di-GMP binding-defective mutant N5MapZR10A can interact with HemK to inhibit the methylation of the class 1 translation termination release factor PrfA. Additionally, we found that HemK plays an important role in Xcc pathogenesis, as the deletion of hemK leads to extensive phenotypic changes, including reduced virulence in citrus plants, decreased motility, production of extracellular enzymes and stress tolerance. Gene expression analysis has revealed that c-di-GMP and the HemK-mediated pathway regulate the expression of multiple virulence effector proteins, uncovering a novel regulatory mechanism through which c-di-GMP regulates Xcc virulence by mediating PrfA methylation via the single-domain PilZ adaptor protein N5MapZ.